Preoperative anemia is associated with prolonged hospital stay and increased facility discharges after glioblastoma resection - Almekkawi, Ahmad K.; Adenwalla, Ammar; Caruso, James P.; Hicks, William H.; Rail, Benjamin; Bagley, Carlos A.; Breshears, Jonathan D.; El Ahmadieh, Tarek Y.; Garzon-Muvdi, Tomas; Goldlust, Samuel A. (Frontiers in Surgery, 2025)
BackgroundDespite numerous operative and non-operative treatment modalities, patients with glioblastoma (GBM) have a dismal prognosis. Identifying predictors of survival and recurrence is an essential strategy for guiding treatment decisions, and existing literature demonstrates associations between hematologic data and clinical outcomes in cancer patients. As such, we provide a novel analysis that examines associations between preoperative hematologic data and postoperative outcomes following GBM resection.MethodsWe performed a retrospective analysis of patients who underwent GBM resection from January 2016 to December 2020. Standard demographic and clinical variables were collected, including pre-operative complete blood count (CBC), and inferential analyses were performed to analyze associations between CBC parameters and postoperative outcomes.ResultsOne hundred and eighty nine (189) patients met inclusion criteria, with a mean age of 60.7 years. On multivariate regression analysis, controlling for age, gender, and performance status, we observed trends suggesting anemic patients may have longer lengths of stay (t statistic = 3.23, p = 0.0015) and higher rates of discharge to inpatient facilities [OR 3.01 (1.09–8.13), p = 0.029], though these associations did not reach statistical significance after correction for multiple comparisons (Bonferroni-corrected significance threshold p < 0.01).ConclusionPreoperative anemia may be a useful pre-operative predictor of postsurgical GBM outcomes. Further study is required to determine whether pre-operative hemoglobin optimization can improve postoperative clinical outcomes, and whether other hematologic and inflammatory markers are predictive of postoperative recovery and functional status.